PAVLE ŠEROGLIĆ’S COMMENTARY OF AUSTRIAN CIVIL CODE - Stanković, Uroš (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
The article presents the commentary on the Austrian Civil Code written by the first reviewer of Serbian Civil Code Pavle Šeroglić (1800–1857). As shown by the contents of some of its parts, the commentary was made between 1 June 1848 and 7 May 1850. In the process of writing the commentary, Šeroglić used both literature and legal acts. The book Šeroglić most frequently relied on was the work titled “Manual for Austrian General Civil Law” (Handbuch des österreichischen allgemeinen Civil- Rechtes, Wien 1846), written by the Vienna lawyer Joseph Ellinger. The legal acts used in the commentary included Austrian and foreign codes and legislative acts, as well as Austrian by-laws. The commentary contains explanatory texts on 734 out of 1502 articles of the Austrian Civil Code. Most of the explanatory texts were placed in the titles on lien law, loan contract and marriage contract. On the other hand, Šeroglić provides no commentary at all in titles dedicted to bailment contract, commodatum contract and accession as a mode of acquiring property. The majority of Serbian legal terms present in the commentary had already existed in Serbian legal language but some of the expressions used by Šeroglić were literally translated from German. There are also terms probably coined by Šeroglić himself. Šeroglić’s commentary has several defects: wrong translations, terminological inconsistency, insufficiently differentiated terminology, and complicated writing style. Based on the sources that Šeroglić used in writing the commentary and the structure of its text, it may be concluded that the commentary was primarily intended for practice rather than theoretical consideration. Judging by the contents of the commentary, its author was well acquainted with social environment and the level of education of the intended readership, the inhabitants of the Military Frontier. However, Šeroglić did not excel at language skills, the proof of which are mistranslations and wrongly coined legal terms.